ChemInform Abstract: Total Synthesis of Crotophorbolone. Issue 15 (24th March 2016) - Asaba, Taro; Katoh, Yuki; Urabe, Daisuke; Inoue, Masayuki
Abstract: The tricyclic crotophorbolone (I) is constructed by coupling of simple fragments.